Permeability and other film properties of plastics and elastomers. (Plastics Design Library, 1995)
This handbook is a database reference ranging in coverage from the barrier and film properties of plastics and elastomers to detailed discussions and test results. Data presented details the differences in permeation between generic families of plastic and rubber materials. Also covered are differences within the same generic family due to environmental factors like temperature and humidity or material characteristics, such as sample preparation and material composition. This data serves as an indication of how one material is likely to behave relative to another material or relative to the same material exposed under different conditions. This includes details of test methods, test conditions, penetrant, sample size, material composition and other factors.
Chiefly tables.
Includes indexes.
Keywords: Plastics -- Permeability -- Tables.; Elastomers -- Permeability -- Tables.; elektronické knihy; electronic books